2017
DOI: 10.1002/celc.201700627
|View full text |Cite
|
Sign up to set email alerts
|

Edge‐Abundant Porous Fe3O4 Nanoparticles Docking in Nitrogen‐Rich Graphene Aerogel as Efficient and Durable Electrocatalyst for Oxygen Reduction

Abstract: A novel Fe3O4 nanoparticles/nitrogen‐doped graphene aerogel (denoted as Fe3O4@NGA) hybrid material with high porosity was prepared by using iron‐based metal‐organic frameworks (MOFs), [Fe3O(H2N‐BDC)3] (H2N‐BDC=2‐aminoterephtalic acid), denoted as MIL‐88B‐NH2, as templates and nitrogen‐doped graphene aerogel (NGA) as the substrate. The obtained Fe3O4 nanoparticles demonstrate a rich edge area with abundant exposed active sites and defects, indicating great potential for oxygen adsorption and activation. When us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 48 publications
0
18
0
1
Order By: Relevance
“…However, the sluggish oxygen reduction reaction (ORR) has severely restrained the potential commercialization of fuel cells, which requires the usage of expensive and fuel‐vulnerable platinum (Pt) based catalysts. Therefore, numerous carbon‐based nanomaterials have been developed to replace the Pt based composites . Among them, the nitrogen species coordinated first‐row transition metal (e.g., Co, Ni, and Fe) atoms in carbons (M–N–C) are widely considered as promising electrocatalysts for ORR .…”
Section: Methodsmentioning
confidence: 99%
“…However, the sluggish oxygen reduction reaction (ORR) has severely restrained the potential commercialization of fuel cells, which requires the usage of expensive and fuel‐vulnerable platinum (Pt) based catalysts. Therefore, numerous carbon‐based nanomaterials have been developed to replace the Pt based composites . Among them, the nitrogen species coordinated first‐row transition metal (e.g., Co, Ni, and Fe) atoms in carbons (M–N–C) are widely considered as promising electrocatalysts for ORR .…”
Section: Methodsmentioning
confidence: 99%
“…MOFs have been widely studied as functional materials for various applications including selective gas adsorption and separation, hydrogen storage, chemical sensors, heterogeneous catalysis, and drug delivery, due to their unique and advantageous characteristics including high surface area, regular and tunable pore structures, diversity in the chemical compositions of the organic linkers and metal nodes, facile synthesis, as well as the controllable chemistry and functionality . Recently, MOF‐based materials, including pristine MOFs, MOF composites (e.g., Pt nanoparticles@MOF and MOF/graphene composite), and MOF‐derived materials, have attracted numerous interests in the field of energy storage and conversion . There have been many excellent reviews published by us and others mainly focusing on MOF‐derived materials such as carbon, metal/carbon, and metal oxide materials for various energy storage and conversion applications .…”
Section: Introductionmentioning
confidence: 99%
“…Metal-organic frameworks (MOFs) are crystalline porous materials that have also been widely employed for these energy-conversion reactions because of their unique characteristics,including their organic-inorganic hybrid nature,large surface area, well-defined porosity,tunable chemical composition, and adjustable functionality. [28][29][30][31][32][33][34][35][36][37][38][39] It has been shown that atomically dispersed metal sites (ADMSs) in MOFs and MOF-derived materials played very important roles on both the photocatalysis and electrocatalysis of the energy-conversion reactions.F or electrocatalytic reactions,the ADMSs not only serve as active sites to adsorb and activate the reactive molecules (e.g. H 2 O, O 2 ,C O 2 ), but also act as redox-active sites to promote the reduction or oxidation of the adsorbed molecules.F or photocatalytic reactions,w ell-studied homogeneous metal complexes can be uniformly anchored or encaged in the nitrogen-containing ligands or pores in MOFs to afford heterogeneous ADMSs incorporated in MOFs, which can serve as photosensitizers or catalysts for efficient and durable photocatalysis.…”
Section: Introductionmentioning
confidence: 99%